can someone explain the underlined steps?
-how does the top line reduce to u-1 in the numerator. isnt (u+1) - 1 = u
-bottom line - is it just a "u" substitution?
thanks
the -1 is brought inside the brackets using $\displaystyle -1=-\frac{2}{2}$
then we have 0.5 multiplied by 2 seperate terms
so they can be brought inside with 0.5 as common factor
$\displaystyle \frac{1}{2}(u+1)-1=\frac{1}{2}(u+1)-\frac{2}{2}=\frac{1}{2}(u+1)+\frac{1}{2}(-2)$
and now $\displaystyle \frac{1}{2}$ is a common factor
so the -2 can be brought inside the brackets.